2020
DOI: 10.1136/bmjopen-2019-032997
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of multidisciplinary simulation-based team training on patients, staff and organisations: protocol for a stepped-wedge cluster-mixed methods study of a national, insurer-funded initiative for surgical teams in New Zealand public hospitals

Abstract: IntroductionNetworkZ is a national, insurer-funded multidisciplinary simulation-based team-training programme for all New Zealand surgical teams. NetworkZ is delivered in situ, using full-body commercial simulators integrated with bespoke surgical models. Rolled out nationally over 4 years, the programme builds local capacity through instructor training and provision of simulation resources. We aim to improve surgical patient outcomes by improving teamwork through regular simulation-based multidisciplinary tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…[7][8][9][10][11] As there is a great need in improving patient safety and healthcare quality, team training has been widely recognised to enhance teamwork. [12][13][14][15] However, health professionals today are not competent in teamwork, and team training has not attracted the attention of medical institutions. [16][17][18] The Chinese Hospital Association has reported that adverse patient events consumes extensive medical resources every year in Chinese healthcare institutions.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] As there is a great need in improving patient safety and healthcare quality, team training has been widely recognised to enhance teamwork. [12][13][14][15] However, health professionals today are not competent in teamwork, and team training has not attracted the attention of medical institutions. [16][17][18] The Chinese Hospital Association has reported that adverse patient events consumes extensive medical resources every year in Chinese healthcare institutions.…”
Section: Introductionmentioning
confidence: 99%
“…However, they also provide testimony to the challenges faced in anaesthesia: anaesthetists are often required to undertake parallel processing in relation to current, previous and impending patients, while also teaching, continuously assessing dynamic clinical situations and at the same time interacting with surgeons and other staff. NetworkZ and the Effective Management of Anaesthetic Crises courses are examples of important initiatives to improve communication and the management of factors such as these during anaesthesia in general, 25,26 but perhaps more thought is needed on how to do this effectively in the context of medication management in particular. Many of the reported medication errors had no consequence.…”
Section: Discussionmentioning
confidence: 99%
“…The theme of communication failures comes through strongly in our data, and this can be addressed by training in teamwork and communication, in concert with promoting the importance of these skills within departments and institutions. 25,26,49 The problem of flushing residual medication from IV lines is simply a failure in technique, and (again anecdotally) has been addressed in some institutions by an interdepartmental focus on this point of practice and the use of checklists at handover to the PACU. Somewhat similar comments apply to wrong-sided regional blocks.…”
Section: Discussionmentioning
confidence: 99%
“…Further detail about NetworkZ courses, debriefing, instructor training, and implementation strategy is available elsewhere. 14 …”
Section: Methodsmentioning
confidence: 99%
“…NetworkZ is a multidisciplinary simulation-based in situ team training program for operating theater staff in public hospitals throughout New Zealand. 14 Its primary objective is to improve patient safety by enhancing interprofessional communication and teamwork. During the in situ simulation scenarios, systems and situational factors that may threaten patient safety were also identified.…”
mentioning
confidence: 99%